Biotribological investigation of amorphous carbon coatings in hard-on-soft contact for biomedical applications - Rothammer, Benedict; Neusser, Kevin; Bartz, Marcel; Wartzack, Sandro; Marian, Max (DKOU 2024, 2024)
Objectives: Amorphous carbon (DLC) coatings deposited on the articulating surfaces of total joint replacements (TJRs) have the potential to enhance the biotribological behavior and longevity [1]. Therefore, we employ an ultrahigh molecular weight polyethylene (PE) ball-on-three titanium (Ti) alloy pin configuration lubricated by simulated body fluid to effectively carry out screening tests. Thus, the influence of the choice of the coated component (Ti and/or PE) were studied. Furthermore, coatings deposited either on the metallic or on both contacting partners (metal/metal or polymer/metal) have been studied in literature so far [2], [3]. Yet, there is a lack of fundamental investigations on the influence of the choice of the coated component. Moreover, non-sterilized PE has mostly been considered in the literature as polymeric substrate and the transfer to coating HXLPE, which is expected to predominate in the future, has been insufficiently examined. Methods: Within this contribution, the influence of aforementioned variations in the configurations are addressed by means of two different DLC coatings applied to polymeric (HXLPE and PE) and/or Ti substrates in a higher stressed and a more moderate load case under peri-implant boundary conditions. The wear rates were determined using laser scanning microscopy. Also, the materials, coating characterization, and biotribological testing are presented and discussed in the light of the corresponding results. Results and conclusion: The DLC coatings featured excellent mechanical properties with a substantial enhancement of indentation hardness and modulus. The adhesion of the coatings as determined in modified scratch tests was considered as very good to PE and as still good to Ti, thus confirming the potential for the use in TJRs. Although the coatings predominantly lead to an increase in friction due to the considerably higher roughness, wear was substantially reduced. Due to higher hardness and good adhesion, this applied to DLC-coated PE against DLC-coated Ti, with up to 80% reduction in ball wear and up to 99% reduction in pin wear compared to uncoated references. While only the metallic components were mostly coated in studies reported in literature, our study showed that coating the PE component in particular is of decisive importance for enhancing the wear performance and increasing the service life of TJRs. Moreover, single sided coating resulted in higher wear of the uncoated counterpart. In the future, this should be considered when assessing coatings for biomedical hard/soft pairings and, in particular, coatings deposited on both articulating surfaces, polymeric and metallic, should be pursued and further optimized. References 1. Skjöldebrand C, Tipper JL, Hatto P, Bryant M, Hall RM, Persson C. Current status and future potential of wear-resistant coatings and articulating surfaces for hip and knee implants. Mater Today Bio. 2022 Apr 30;15:100270. DOI: 10.1016/j.mtbio.2022.100270 2. Rothammer B, Neusser K, Marian M, Bartz M, Krauß S, Böhm T, Thiele S, Merle B, Detsch R, Wartzack S. Amorphous Carbon Coatings for Total Knee Replacements-Part I: Deposition, Cytocompatibility, Chemical and Mechanical Properties. Polymers (Basel). 2021 Jun 11;13(12):1952. DOI: 10.3390/polym13121952 3. Rothammer B, Marian M, Neusser K, Bartz M, Böhm T, Krauß S, Schroeder S, Uhler M, Thiele S, Merle B, Kretzer JP, Wartzack S. Amorphous Carbon Coatings for Total Knee Replacements-Part II: Tribological Behavior. Polymers (Basel). 2021 Jun 5;13(11):1880. DOI: 10.3390/polym13111880